2004
DOI: 10.1021/ac0486995
|View full text |Cite
|
Sign up to set email alerts
|

Sol−Gel Derived Potentiometric pH Sensors

Abstract: A potentiometric sol-gel derived (xerogel) pH sensor based on covalently attached amine groups is described. The sensor consists of a Ag/AgCl electrode coated with a hybrid aminosilane/alkylsilane xerogel film. Various combinations of aminosilanes and alkylsilanes are evaluated for their potentiometric response to pH. The optimal sensor design is composed of (aminoethylaminomethyl)phenethyltrimethoxysilane and methyltrimethoxysilane. This sensor exhibits near-Nerstian response (-55 mV.decade(-)(1)), responds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In contrast, sub-Nernstian behavior (−42.23 mV/decade) was observed for sensors prepared with PEDOT-PEG membranes. The decrease in the response slope in hydrophilic and charge density surfaces, as in the case of this PEG-modified surface, has been reported on alkylsilane-modified potentiometric pH sensors [18,19]. As reported charged and conductive polymers have more difficulties to achieve a great selectivity in ISE membrane.…”
Section: Resultssupporting
confidence: 58%
“…In contrast, sub-Nernstian behavior (−42.23 mV/decade) was observed for sensors prepared with PEDOT-PEG membranes. The decrease in the response slope in hydrophilic and charge density surfaces, as in the case of this PEG-modified surface, has been reported on alkylsilane-modified potentiometric pH sensors [18,19]. As reported charged and conductive polymers have more difficulties to achieve a great selectivity in ISE membrane.…”
Section: Resultssupporting
confidence: 58%
“…Amine-terminated xerogels have previously been used in the production of multiple optical (e.g., pH), 29 amperometric (e.g., CO 2 , NO) 30,31 and enzyme-based (e.g. glucose) 32,33 sensors and biosensors.…”
Section: Mn II (No)tpps Formation In Xerogel Filmsmentioning
confidence: 99%
“…The electrode lifetime was investigated by performing the calibration curve and the periodical testing of standard solutions (1x10 -6 -1x10 -2 M PRED) and calculating the response slopes. It was observed that the proposed electrodes exhibited good stabilities in terms of slope in the linear domain of concentration and the electrodes can be used continually for about 1.5 months without considerable decrease in its slope value [25].…”
Section: Life Time Of the Ion Selective Electrodementioning
confidence: 94%